1990
DOI: 10.1002/ldr.3400020102
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microbiological treatment for restoration of oil contaminated soil

Abstract: This paper describes the laboratory development of a microbial treatment for soil contaminated with oil hydrocarbon residues at a disused refinery site and the application of this technology in a pilot scale treatment bed in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A large number of technologies have been developed in order to clean up such sites. However, in some cases, biomonitoring has emerged as one of the most effective remediation strategies, especially where contaminant plumes can be retained within property boundaries in the subsurface and groundwater [ 3 ]. This has created a need for a variety of monitoring technologies, ranging from simple and rapid on-site assessments to elaborate laboratory measurements of contaminants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of technologies have been developed in order to clean up such sites. However, in some cases, biomonitoring has emerged as one of the most effective remediation strategies, especially where contaminant plumes can be retained within property boundaries in the subsurface and groundwater [ 3 ]. This has created a need for a variety of monitoring technologies, ranging from simple and rapid on-site assessments to elaborate laboratory measurements of contaminants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of a range of pollutant compounds in various soil systems using either proprietary nutrients alone or proprietary nutrients with specific microbial inocula relative to a control is shown in Figure 1 (Ellis and Bewley, 1990). Substantial reductions were obtained by the addition of specific nutrients, but in most cases both the rate and extent of degradation were enhanced by bioaugmentation.…”
Section: Case Study 1: Bench Scale Treatability Testingmentioning
confidence: 99%
“…Several studies have shown a moderate level of success with the use of prepared bed/on-site remediation strategies on PAH contaminated soil (21,22,46,103,128,141,142). Overall, prepared bed/on-site remediation was found to degrade LMW PAHs relatively efficiently compared to in situ remediation.…”
Section: Biological Degradation Of Pahsmentioning
confidence: 97%